2004
DOI: 10.1111/j.1365-2141.2004.05085.x
|View full text |Cite
|
Sign up to set email alerts
|

Preserved granulocyte formation and function, as well as bone marrow innervation, in subjects with complete spinal cord injury

Abstract: SummaryPatients with a spinal cord injury are at risk of infections and is partly attributed to immobilization. Their lymphocyte-mediated immunity is impaired and the growth of blood progenitor cells is reduced. An adequate immune response depends on granulocytes being mobilized rapidly and activated properly, at the inflammatory site. Possibly this requires a coordinated interaction between the autonomous nervous system and cells within the haematopoietic bone marrow. Granulocyte function in the spinal cord i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…However, B lymphopoiesis recovered within 4 weeks despite continued elevation of corticosterone in chronically injured mice. These observations are consistent with those in chronic SCI patients, who have normal numbers of bone marrow lymphocytes despite elevated stress hormones (41, 42). Accordingly, transiently reduced B lymphopoiesis likely reflects additional or alternative mechanisms.…”
Section: Discussionsupporting
confidence: 89%
“…However, B lymphopoiesis recovered within 4 weeks despite continued elevation of corticosterone in chronically injured mice. These observations are consistent with those in chronic SCI patients, who have normal numbers of bone marrow lymphocytes despite elevated stress hormones (41, 42). Accordingly, transiently reduced B lymphopoiesis likely reflects additional or alternative mechanisms.…”
Section: Discussionsupporting
confidence: 89%
“…Surprisingly though, little is known about changes of blood and bone marrow cell numbers after SCI, despite the fact that immune functions are often impaired and that infection is a major cause of death after SCI ( al., 1992; Iverson et al, 2004). The present results clearly showed significant decreases of total leukocytes with lymphocytes and eosinophils decreased at all time points post-Tx in both blood and bone marrow.…”
Section: Differentially Modulated Immune Cells Post-scisupporting
confidence: 50%
“…13,14 Spinal cord injury in humans presents a unique opportunity to study possible early release of progenitors from the bone marrow in subjects with injury to the central nervous system. 15 Iversen et al, 15,16 after two studies, concluded that terminal differentiation of immune cells did not require supraspinal control; however, more investigation was needed to fully explore this possibility.…”
Section: Discussionmentioning
confidence: 99%